Bond between CFRP rod panels and concrete using cementitious mortar. (28th February 2020) - Jawdhari, Akram; Fam, Amir; Harik, Issam
Highlights: 44 notched-beam bond tests to evaluate cementitious mortar in bonding CFRP rod panels (CRPs) to concrete. Mortar resulted in ultimate load ( Pult. ) 86% that from epoxy, with a ductile rod slipping failure. Pult. of CRP was 1.17 and 7 times that of flat CFRP plate, for epoxy and mortar, respectively. A development length and bond strength of 125 mm and 460 kN/m, respectively, were found for mortar-bonded CRP. Effects of width ratio, rod spacing-to-diameter ratio, and rod diameter, rod surface condition, were investigated. Abstract: Carbon-FRP rod panels (CRPs), generated from small diameter rods mounted on a fiberglass mesh, are becoming a viable retrofit option. The gaps between rods enable full encapsulation by adhesive, thereby enhancing bond to existing concrete members, compared to flat plates. Existing studies focused on epoxy adhesive. In this study, 44 notched-beam bond tests, were carried out to investigate the effectiveness of cementitious mortar in bonding CRP to concrete and to examine the effects of a number of material and geometric parameters, comparing CRP to flat plates and mortar to epoxy. Results showed that the mortar was able to achieve a comparable ultimate load ( Pult. ), 86% that of epoxy, and a much more ductile failure by gradual rod slippage from the mortar. Compared to an equivalent CFRP plate, Pult. of CRP was 1.17 and 7 times, respectively, for epoxy and cementitious mortar. Brittle debonding failure dominated in CRP with epoxy and in CFRP plate with both epoxy and mortar. Pult was found to vary linearly with the bond length of CRP, up to a development length of 125 mm. A value of 460 kN/m can be assumed for bond strength. Rod axial stress ( σf ) increased by 42%, when CRP panel-to-concrete width ( bf /bc ) ratio increased from 0.25 to 0.5; decreased linearly by 13% when rod spacing-to-diameter ( S / D ) ratio increased from 3 to 8; decreased by 76% when rod diameter D increased from 2 to 4 mm. Sand coating the smooth rod resulted in a 45% increase in σf of the 4 mm rods but not the 2 mm rods, although failure shifted from gradual slippage to sudden debonding.